Fatal Acute Motor Axonal Neuropathy Induced by Nivolumab: A Case Report and Literature Review - Yildirim, Nilgun; Gonen, Murat; Balgetir, Ferhat; Er, Muhammed Burak (Cig Media Group, Lp, 2019)
Clinical Practice Points Nivolumab is a monoclonal antibody that inhibits the programmed cell death receptor-1 and has become one of the standardized treatments for patients with advanced stage renal cell cancer because of long-term disease control and prolonged general survival in suitable patient groups. The most important side effect is immune-related adverse events. In this study, we describe a case of fatal paraparetic acute motor axonal neuropathy (AMAN) following nivolumab treatment. A patient was diagnosed with metastatic papillary renal cell carcinoma, and nivolumab treatment was initiated. Nearly complete response was obtained after 5 courses. After 6 courses of nivolumab treatment, he developed muscle weakness of the upper and lower limbs. His limb weakness rapidly progressed, and he became bed-bound. After the neurologic examination, he was diagnosed with AMAN, a variant of Guillain-Barre Syndrome. Methylprednisolone 250 mg/day and intravenous immunoglobulin were initiated in the patient, who was suspected to have an immune-related adverse event that was secondary to nivolumab treatment. Nivolumab treatment was discontinued. The patient was unresponsive, and he died on the 25th day after the symptoms appeared for the first time. Our case is the first serious case of peripheral neuropathy owing to nivolumab use in renal cell carcinoma. The side effect of AMAN in this case has not been reported to date. With the increasing use of these drugs, more adverse effects will be reported in the near future, so clinicians need to be more careful in terms of their neurologic toxicity, as well.
Keywords: Immune-related adverse events; Immunotherapy; Polyneuropathy; Renal cell cancer; Treatment